Plasmodium berghei sporozoites in nonreplicative vacuole are eliminated by a PI3P‐mediated autophagy‐independent pathway. (8th October 2020) - Bindschedler, Annina; Wacker, Rahel; Egli, Jessica; Eickel, Nina; Schmuckli‐Maurer, Jacqueline; Franke‐Fayard, Blandine M.; Janse, Chris J.; Heussler, Volker T.
Abstract: The protozoan parasite Plasmodium, causative agent of malaria, invades hepatocytes by invaginating the host cell plasma membrane and forming a parasitophorous vacuole membrane (PVM). Surrounded by this PVM, the parasite undergoes extensive replication. Parasites inside a PVM provoke the Plasmodium ‐associated autophagy‐related (PAAR) response. This is characterised by a long‐lasting association of the autophagy marker protein LC3 with the PVM, which is not preceded by phosphatidylinositol 3‐phosphate (PI3P)‐labelling. Prior to productive invasion, sporozoites transmigrate several cells and here we describe that a proportion of traversing sporozoites become trapped in a transient traversal vacuole, provoking a host cell response that clearly differs from the PAAR response. These trapped sporozoites provoke PI3P‐labelling of the surrounding vacuolar membrane immediately after cell entry, followed by transient LC3‐labelling and elimination of the parasite by lysosomal acidification. Our data suggest that this PI3P response is not only restricted to sporozoites trapped during transmigration but also affects invaded parasites residing in a compromised vacuole. Thus, host cells can employ a pathway distinct from the previously described PAAR response to efficiently recognise and eliminate Plasmodium parasites. Abstract : This study identified a new host cell response which targets Plasmodium sporozoites residing in transient or compromised vacuoles. This response is characterized by PI3P‐labeling of the surrounding membrane followed by lysosomal acidification of the parasites.